Cytotoxicity of three Orchid species extracts against HeLa, MCF-7, and T47D cancer cells - Syamsurizal; Utami, Diah Tri; Fitrianingsih; Maharini, Indri; Prabowo, Beni Hendro (Proceedings Academic Universitas Jambi, 2025)
Background: Cancer remains a leading cause of death globally, necessitating the search for novel therapeutic agents from natural sources. Orchids, known to produce diverse secondary metabolites, hold significant potential. Objective: This study aims to evaluate and quantitatively compare the in vitro cytotoxicity activity of crude methanol extracts from three orchid species against HeLa, MCF-7, and T47D cells using the MTT assay. Methods: This study investigated the comparative in vitro cytotoxic activity of crude methanol extracts from three native orchid species, Cymbidium sp., Grammatophyllum speciosum, and Dendrobium crumenatum, against three human cancer cell lines: HeLa (cervical), MCF-7 (breast), and T47D (breast). Cytotoxicity assessment was performed using the MTT Assay. The extracts were tested at various concentrations to determine their inhibitory concentrations IC50.Results: The results showed that the three orchid extracts exhibited varying cytotoxic effects across the tested cell lines. Significantly, the crude methanol extract of Dendrobium crumenatum showed the most promising activity, especially against MCF-7 breast cancer cells, with an IC50 value of 126.58±5.50 µg/mL. The activity against HeLa and T47D was less potent. These findings indicate that secondary metabolites in Dendrobium crumenatum have selective antiproliferative properties. Conclusion: In conclusion, the methanol extract of Dendrobium crumenatum is a potential candidate for the isolation and further identification of active compounds in developing anticancer drugs, especially for breast cancer.